Problems of Personal Communication Using a European Language Among Sudanese Immigrants in Application to the English Language (The International Journal for Scientific Research, 2023)
This study aimed to show the problems faced by the sample members when they carried out personal communication using English, one of the European languages spoken by the countries hosting Sudanese immigrants. The quantitative and qualitative approaches were applied, and the questionnaire was distributed to the selected sample, which numbered 100 people. The most important findings are that most of the study sample's ages ranged between 35 and less than 45, and this category is classified as one of the active groups that can integrate into the indigenous societies in the host country. University degree holders form the highest percentage among the study sample, among them doctors and engineers, and most of them believe that communicating with others using the language of the host country is important. Their presence in the host country led nearly half of the study sample to strongly agree that learning the language in their country helped form a building block for learning the language in the host country, and nearly three-quarters of the sample believe that the solution to communication problems with others is speaking in English and minimizing speaking to Arabic speakers. This study recommends the necessity of carrying out more studies in this field due to its scarcity and the consideration of different angles in this study, especially since the number of immigrants from Sudan is on the rise due to many circumstances, including political, economic, social, and security. Using relevant authorities for such studies and implementing their findings and recommendations, which have led to many solutions to problems in this field.
Keywords: Personal communication; Sudanese Immigrant; English Language